1998
DOI: 10.1046/j.1365-2265.1998.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal status is an important determinant of bone density in acromegaly

Abstract: Eugonadal acromegalic patients have increased lumbar spine and femoral neck BMD compared to hypogonodal acromegalic patients and the general population, but it is reduced if patients have been hypogonadal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 27 publications
2
62
1
2
Order By: Relevance
“…Details on gonadal status in patients and controls are given in Table 1. The duration of acromegaly (nZ55) was estimated to be (mean and range) 8 years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The study was approved by the local ethical committee and conducted according to the Declaration of Helsinki II.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details on gonadal status in patients and controls are given in Table 1. The duration of acromegaly (nZ55) was estimated to be (mean and range) 8 years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The study was approved by the local ethical committee and conducted according to the Declaration of Helsinki II.…”
Section: Subjectsmentioning
confidence: 99%
“…In fact, acromegaly was traditionally associated with osteoporosis (12)(13)(14). Later studies have revealed a differential effect of GH excess on the axial (70% trabecular bone) and appendicular skeleton (90% cortical bone) with unchanged or reduced vertebral bone density and increased forearm bone density (1,3,(13)(14)(15)(16)(17), while some studies show no differences in acromegalic patients compared with normal controls (4,18,19). However, measurement of bone mineral density (BMD) in the axial skeleton, as an indicator of trabecular bone mass, may be overestimated in endocrine disorders affecting bone size and the distribution between trabecular and cortical envelopes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that the anabolic effects of GH on bone mineral density (BMD) may be sustained after cure of acromegaly (1)(2)(3)(4)(5), but duration of follow-up was relatively short in the majority of studies. The effects of GH excess on BMD appear to be less consistent.…”
Section: Introductionmentioning
confidence: 99%
“…In active acromegaly, high circulating concentrations of GH and IGF1 are associated with increased cortical BMD (6)(7)(8)(9)(10). The reported effects of GH/IGF1 excess on trabecular BMD are more variable, with studies reporting either increased or decreased BMD at trabecular sites possibly due to the variable presence of hypogonadism (1,(3)(4)(5)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%